2011
DOI: 10.5012/bkcs.2011.32.9.3443
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies on the Oxidation of Catechin in Aqueous Solution

Abstract: The spectroscopic behavior of catechin (5,7,3',4'-tetrahydroxyflavan-3-ol), has been studied in the presence and the absence of air using UV-vis absorption spectrophotometry and fluorescence spectroscopy. The UV-vis absorption spectrum of catechin shows a very sharp and strong absorption maximum peak at 275 nm in deaerated water. New absorption maximum peaks appeared in aerated water, as well as in basic aqueous solution, caused by the oxidation of catechin. The absorbances in the UV-vis absorption spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…During the oxidation of catechin at high pH, the catechol moiety dissociates first yielding the ionic form, which subsequently undergoes oxidation leading to the formation of the quinoid form (Bark et al . ). The formed quinones are electron acceptors (Suchetti et al .…”
Section: Resultsmentioning
confidence: 97%
“…During the oxidation of catechin at high pH, the catechol moiety dissociates first yielding the ionic form, which subsequently undergoes oxidation leading to the formation of the quinoid form (Bark et al . ). The formed quinones are electron acceptors (Suchetti et al .…”
Section: Resultsmentioning
confidence: 97%
“…19 The solution did not display a yellowish color, even though it was left in the dark at room temperature…”
Section: Resultsmentioning
confidence: 99%
“…Some papers reported that oxidation of catechin is mainly carried out in the dissociation of catechol moiety in the initial state. 7,19 It might be therefore concluded that the -OH part of the catechol moiety bound to catechin molecule is first dissociated its anion form and then the ionized chemical species are converted into the oxidized form called quinones receiving help from metal ions.…”
mentioning
confidence: 99%
“…The assumption that (+)-catechin (analogue of catechol) is a substrate for laccase Trametes versicolor was confirmed by the change of colour of the supporting electrolyte to yellow during cyclic voltammetry at the CPE/Laccase biosensor (not shown), which was caused by formation of (+)-catechin quinone [22,23]. This phenomenon was not observed at the bare CPE with the same working conditions.…”
Section: Final Discussion and Confirmation Of Obtained Resultsmentioning
confidence: 87%